Assessment of Physical Activity and Cardiorespiratory Fitness in Medical Students (Med Phoenix, 2022)
Introduction: Cardiorespiratory fitness is an indicator of cardiovascular health, usually expressed as VO2max. VO2max is the capacity of our body to transport and utilize oxygen during maximal exertion. The present study attempts to assess the level of physical activity and cardiorespiratory fitness in medical students and compare VO2max between physically active and insufficiently active students.Materials and Methods: An observational cross sectional study was conducted in 246 medical students (123 males and females each) of age between 18 to 23 years in National Medical College, Birgunj. After obtaining ethical clearance, screening was done with American College of Sports Medicine participants screening questionnaire. Students were classified as physically active and insufficiently active by using Global Physical Activity Questionnaire. VO2max was calculated from recovery heart rate counted from fifth to twentieth second of recovery after step test. Finally, subjects were categorized into different level of cardiorespiratory fitness based on their VO2max values.Results: Present study found 33.6% of insufficiently physical active students. Females had higher prevalence of insufficient physical activity (40.6%) than males (26.8%). The VO2max of male and female was 46.79 ± 8.98 and 36.15 ± 4.66 ml/Kg/min respectively. Majority of female participants had ‘average’ VO2max whereas in male, distribution is almost equal in ‘excellent’, ‘good’ and ‘fair’ category.Conclusion: Around one-third of medical students did not meet the level of physical activity recommended by WHO for health. Majority of them had ‘average’ level of VO2max and those physically active had better cardiorespiratory fitness.